2016
DOI: 10.1084/jem.20151722
|View full text |Cite
|
Sign up to set email alerts
|

IFN-γ receptor and STAT1 signaling in B cells are central to spontaneous germinal center formation and autoimmunity

Abstract: B cell–intrinsic IFN-γ receptor signaling through STAT1 is required for the generation of spontaneous germinal centers, which can lead to pathogenic autoantibody production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
166
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(181 citation statements)
references
References 63 publications
11
166
3
1
Order By: Relevance
“…Others have previously reported different requirements for GC formation in spontaneous autoimmunity versus deliberate immunization, with IFN-γR needed for the former but not the latter event (30,31). These observations, together with another observation that TLR7 expression in B cells is needed for GC appearance in spontaneous autoimmunity (39), are in line with our findings with respect to T-bet + ABCs, since ABC formation depends on IFN-γ and TLR7 signaling in B cells (11).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Others have previously reported different requirements for GC formation in spontaneous autoimmunity versus deliberate immunization, with IFN-γR needed for the former but not the latter event (30,31). These observations, together with another observation that TLR7 expression in B cells is needed for GC appearance in spontaneous autoimmunity (39), are in line with our findings with respect to T-bet + ABCs, since ABC formation depends on IFN-γ and TLR7 signaling in B cells (11).…”
Section: Discussionsupporting
confidence: 92%
“…These observations, together with another observation that TLR7 expression in B cells is needed for GC appearance in spontaneous autoimmunity (39), are in line with our findings with respect to T-bet + ABCs, since ABC formation depends on IFN-γ and TLR7 signaling in B cells (11). However, the results of some others differ from those reported here in one respect, since some, but not all other studies found that T-bet expression in B cells was not required for spontaneous GC formation (30,31).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Spontaneous germinal centre (GC) responses that are associated with autoantibody production are implicated in the pathogenesis of SLE. The pathways through which GC B cell tolerance break down are not clear, but in mouse models it was recently shown that IFN-γR signaling in B cells as well as B cell IFN-γ production were critical initial steps for spontaneous GC development leading to autoimmunity6162. Interestingly, SLE patients also display increased BAFF serum levels that correlate with disease activity63.…”
Section: Discussionmentioning
confidence: 99%
“…Moncef Zouali 1,2 and Gregory Tsay 3,4 Rahman′s data also indicate a critical B cell-intrinsic role of interferon γ receptor (IFNγR) signaling in accentuating Spt-GCs and autoimmune responses in B6.Sle1b mice (4). They suggest that IFNγR and STAT1 signaling control Spt-GC and Tfh formation by driving T-bet expression and IFNγ production by B cells.…”
Section: Developing Connections Among B Lymphocytes and Deregulated Pmentioning
confidence: 95%